2015
DOI: 10.15406/jdhodt.2015.03.00080
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Teledentistry by Brazilian Dentists

Abstract: (WHO); European Union (EU), International Telecomunications Agencies (ITA) and Spacial European Agency (SEA), adopted oficially "eHealth" (eHealth), as an oficial term, after that turnning point different health professions started to use the telehealth, for clinical;administrative and educatonal tools in health [2]. The refletion of the use of tecnology of information (TIs) in public service, has stimulated the dialogue between diferent social actors, compromise with the quality and resolutivity of health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The comparison of results in the literature indicated that knowledge about teledentistry differs by country, level of education, and years of experience [13][14][15][16][17]. Dental students were found to be less knowledgeable and enthusiastic about teledentistry than dental faculty or practicing dentists [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of results in the literature indicated that knowledge about teledentistry differs by country, level of education, and years of experience [13][14][15][16][17]. Dental students were found to be less knowledgeable and enthusiastic about teledentistry than dental faculty or practicing dentists [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies showing that most dentists and dental students wished to practice teledentistry in the future [14,17], approximately 26-31.4% of respondents did not think that teledentistry was efficient in many respects [15][16][17]. The studies also highlighted some barriers to teledentistry implementation that included the high cost of technology, lack of available technology, lack of human resources [17], lack of computer skills among dentists, and need to perform manual work rather than online procedures [18]. Few responses (29.5%) agreed that specialty treatment was possible without any compromise on the quality of care.…”
Section: Discussionmentioning
confidence: 99%